lincRNA‐p21 inhibits hepatic stellate cell activation and liver fibrogenesis via p21 - Jianjian Zheng; Peihong Dong; Yuqing Mao; Shaolong Chen; Xiaoli Wu; Guojun Li; Zhongqiu Lu; Fujun Yu (2015)
Long non‐coding RNA s are involved in various biological processes and diseases. The biological role of long intergenic non‐coding RNA ‐p21 (linc RNA ‐p21) in liver fibrosis remains unknown before this study. In this study, we observed marked reduction of linc RNA ‐p21 expression in mice liver fibrosis models and human cirrhotic liver. Over‐expression of linc RNA ‐p21 suppressed activation of hepatic stellate cells ( HSC s) in vitro . Lentivirus‐mediated linc RNA ‐p21 transfer into mice decreased the severity of liver fibrosis in vivo . Additionally, linc RNA ‐p21 reversed the activation of HSC s to their quiescent phenotype. The mRNA levels of linc RNA ‐p21 and p21 were positively correlated. Our results show that over‐expression of linc RNA ‐p21 promotes up‐regulation of p21 at both the mRNA and protein levels. Furthermore, linc RNA ‐p21 inhibited cell‐cycle progression and proliferation of primary HSC s through enhancement of p21 expression. Compared with healthy subjects, serum linc RNA ‐p21 levels were significantly lower in patients with liver cirrhosis, especially those with decompensation. These findings collectively indicate that linc RNA ‐p21 is a mediator of HSC activation, supporting its utility as a novel therapeutic target for liver fibrosis.